PARTICLEBOARDS PRODUCED WITH EPOXY INK WASTE AND BTH POLYMER AS ADHESIVES - Christoforo,André L. (2018)
ABSTRACT The aim of this research was to analysis the feasibility of production of wood particleboard with two alternative adhesives: epoxy ink waste and polyhydroxybutyrate polymer (BTH). Particleboard were produced with Pinus sp. wood specie wastes from sawmill process. For each alternative adhesive was proposed different combinations of parameters: time and temperature of press, pressure; alternative adhesive content and mass of wood particles. Two alternative adhesive contents were adopted, 10% and 20% replacing ureaformaldehyde adhesive. Mechanical properties (perpendicular tensile strength, pullout strengths of screw on face and top; modulus of elasticity and rupture) were determined according to ABNT NBR 14810:3 Brazilian Standard Code. The obtained results were compared to ABNT NBR 14810:3 and ANSI A.2018:1 Standard Codes requirements values. Particleboards produced with epoxy ink waste showed perpendicular tensile strength according to the minimum Standards requirements values. All proposed combinations to manufacture BTH polymer particleboards didn't show satisfactory mechanical properties in comparison to the Standard Codes values. Other combinations of wood species, time, pressure and temperature, epoxy ink waste and BTH polymer contents should be studied so that the requirements can be met.